Approach to device-detected subclinical atrial fibrillation - Van Zyl, Martin; McLeod, Christopher; Gersh, Bernard (SA Heart Journal, 2017)
Subclinical atrial fibrillation, a commonly encountered entity in patients with implantable devices, has been associated with a number of adverse outcomes – the most important of which is thromboembolism. Through the detection of atrial high rate episodes, implanted devices offer a method to monitor for atrial fibrillation over extended periods of time. Several studies have demonstrated that patients with device-detected atrial tachyarrhythmias have an increased incidence of stroke, especially in the presence of additional risk factors. Yet, there are many uncertainties with limited evidence from randomised clinical studies and no formal guidelines to inform management in this population. This contributes to marked practice heterogeneity, underrecognition and missed opportunities for stroke prevention. We propose a logical approach to management of patients with device-detected atrial high rate episodes pending additional data from ongoing trials.